Conceptualising the Relationship Between Youth, Music and DIY Careers: A Critical Overview. (June 2018) - Bennett, Andy
The purpose of this article is to explore how creative competencies acquired through involvement in music and style-based youth cultures are being converted by young people into DIY (do-it-yourself) careers. This term, as applied here, covers a range of alternative and do-it-yourself modes of work and employment not governed by the acquisition of formal qualifications and training, but, rather, grounded in knowledge and practical know-how acquired through participation in music and style-based youth cultures and associated consumption, leisure and lifestyle practices. The article examines how the emergence of the DIY career can be placed in the context of the collapse of the youth labour market and the increasingly precarious position in which young people find themselves. It also argues that, given the increasing emphasis among youth (and indeed post-youth individuals) placed on the significance of music as a source of DIY career-making, some redefinition of the term DIY music-making and the sphere of DIY creative practice is necessary, particularly in respect of its relationship to more mainstream cultural industries and the related concept of the 'creative city'.